USE OF BLUE-GREEN ALGAE (CYANOBACTERIA) AS BIOFUNGICIDES, BIOSTIMULANTS AND IMPROVE WHEAT RESISTANCE TO ABIOTIC STRESS - HAGGAG WAFAA, M. (International Journal of Pharma and Bio Sciences, 2016)
Wheat is the most important cereal crop, a staple food for more than one third of population world. Recently, there is increased interest in naturally produced active compounds as alternatives of fungicide and improve plant stress. Blue-green algae (cyanobacteria) secondary metabolites have a diverse antagonistic activity that lead to disintegration of microbial growth and improve plant resistant against stress. So, this study was conducted to evaluate the antifungal activities of Oscillatoria agardhii in retarding the growth of wheat pathogenic fungal species and improve resistance to biotic and abiotic stress under stress conditions in compared to the natural environment. Based on zone of inhibition formation and Minimal Inhibitory Concentrations (MIC), it was concluded that the extracts of O. agardhii had significant antifungal and antimicrobial efficacy. Experiment was conducted under natural conditions at farmer’s field in middle of Sinai which saline soil and compared in a natural farm which a normal soil to study the effective use of O. agardhii, resulted in a significantly greater decrease in the diseases incidence of powdery mildew, leaf rust and leaf spots, increased of total soluble protein , proline, soluble carbohydrates, Chlorophyll , carotenoids NPK, K/N ratio in wheat as well as plant growth and yield. The significant increase in grain yield of wheat was observed. Cyanobacteria can be excellent biocontrol sources for plant pathogenic fungi as they can be easily cultured, less expensive compared to synthetic fungicides and ecofriendly, rather they can also promote plant growth. The investigation, certainly points out the necessity of exploring cyanobacterial strains as potentially outstanding sources of antifungal drugs, Biostimulants and anti-stress that improve plant resistance to abiotic stress.